RESIDUAL AND AIR - BORNE EFFECTS OF PIRIMIPHOS - METHYL ON DIFFERENT SURFACES IN SOUTH OF IRAN - "H. Ladonni; M. Motabar; M. Iranpour " (Tehran University of Medical Sciences, 1992)
An investigation was made to study the residual activity and air- borne effect of pirimiphos- methyl, at 2g a.i./m2 in hut scale trials on different surfaces in kazeroun, and Bandar-Abbas, south of Iran. In Kazeroun area, bio-assay contact mortality test with pirimiphos methyl on mud, wood, cement and plaster surfaces, 54 days after hut spraying, decreased from 100% to 46.7%, 61.25%, 36.6% and 40%, respectively. In Baridar-Abbas area, after 72 days of hut spraying, the mortalities on cement and plasters surfaces decreased from 100% to 63.4% and 45.4%, respectively. The fumigation effect of pirirnlphosmcthyl on mud and plaster walls with wooden ceiling were studied in Kazeroun. 'The activity of pirimiphos- methyl on mud and plaster surfaces dropped from 100% to 52% and 46.53% after 54 days of hut spraying respectively. The results suggested that pirimiphos-methyl has effective contact and vapour effect at least for about 50 days on different surfaces in south of Iran.